CH3Cl, CH2Cl2, CHCl3, and CCl4: Infrared spectra, radiative efficiencies, and global warming potentials. (May 2016) - Wallington, Timothy J.; Pivesso, Bruno Pasquini; Lira, Alane Moura; Anderson, James E.; Nielsen, Claus Jørgen; Andersen, Niels Højmark; Hodnebrog, Øivind
Abstract: Infrared spectra for the title compounds were measured experimentally in 700 Torr of air at 295 K and systematically modeled in B3LYP, M06-2X and MP2 calculations employing various basis sets. Calibrated infrared spectra over the wavenumber range 600–3500 cm −1 are reported and combined with literature data to provide spectra for use in experimental studies and radiative transfer calculations. Integrated absorption cross sections are (units of cm −1 molecule −1 ): CH3 Cl, 660–780 cm −1, (3.89±0.19)×10 −18 ; CH2 Cl2, 650–800 cm −1, (2.16±0.11)×10 −17 ; CHCl3, 720–810 cm −1, (4.08±0.20)×10 −17 ; and CCl4, 730–825 cm −1, (6.30±0.31)×10 −17 . CH3 Cl, CH2 Cl2, CHCl3, and CCl4 have radiative efficiencies of 0.004, 0.028, 0.070, and 0.174 W m −2  ppb −1 and global warming potentials (100 year horizon) of 5, 8, 15, and 1775, respectively. Quantum chemistry calculations generally predict larger band intensities than the experimental values. The best agreement with experiments is obtained in MP2(Full) calculations employing basis sets of at least triple-zeta quality augmented by diffuse functions. The B3LYP functional is found ill-suited for calculating vibrational frequencies and infrared intensities of halocarbons. Highlights: Infrared spectra reported for CH3 Cl, CH2 Cl2, CHCl3, and CCl4 . REs of CH3 Cl, CH2 Cl2, CHCl3, and CCl4 are 0.004, 0.028, 0.070, and 0.174 W m −2  ppb −1, respectively. GWPs of CH3 Cl, CH2 Cl2, CHCl3, and CCl4 are 5, 8, 15, and 1775, respectively.